Effect of structural setting of source volume on rock avalanche mobility and deposit morphology - Z. Duan; Z. Duan; Y.-B. Wu; Y.-B. Wu; Q. Zhang; Q. Zhang; Z.-Y. Li; Z.-Y. Li; L. Yuan; L. Yuan; K. Wang; K. Wang; et al. (Solid Earth, 2022)
Deposit morphologies and sedimentary characteristics are methods for investigating rock avalanches. The characteristics of structural geology of source volume, namely the in-place rock mass structure, will influence these two deposit characteristics and rock avalanche mobility. In this study, a series of experiments were conducted by setting different initial configurations of blocks to simulate different characteristics of structural geology of source volume, specifically including the long axis of the blocks perpendicular to the strike of the inclined plate (EP), parallel to the strike of the inclined plate (LV), perpendicular to the inclined plate (LP), randomly (R) and without the blocks (NB) as a control experiment. The experimental materials comprised both cuboid blocks and granular materials to simulate large blocks and matrixes, respectively, in natural rock avalanches. The results revealed that the mobility of the mass flows was enhanced in LV, LP and R configurations, whereas it was restricted in the EP configuration. The mobility decreased with the increase in slope angles at LV configurations. Strand protrusion of the blocks made the elevation of the deposits at LV configuration larger than that at EP, LP and R configurations. A zigzag structure is created in the blocks resulting from the lateral spreading of the deposits causing the blocks to rotate. Varying degrees of deflection of the blocks demonstrated different levels of collision and friction in the interior of the mass flows; the most intensive collision was observed at EP. In the mass deposits, the blocks' orientation was affected by their initial configurations and the motion process of the mass flows. This research would support studies relating characteristics of structural geology of source volume to landslide mobility and deposit morphology.